False vocal cord perforation with abscess treated by negative pressure wound therapy. (April 2020) - Makihara, Seiichiro; Kariya, Shin; Naito, Tomoyuki; Uraguchi, Kensuke; Matsumoto, Junya; Noda, Yohei; Okano, Mitsuhiro; Nishizaki, Kazunori
Perforation of the larynx is very rare but may result in severe airway complications that include pneumothorax, pneumonia, mediastinitis, and retropharyngeal abscess. If conservative treatment fails, aggressive treatments including reconstructive surgery with pedicle flap are considered. Negative pressure wound therapy has been used for large skin defects, necrotizing fasciitis, pharyngocutaneous fistula, stoma dehiscence, osteoradionecrosis of the mandible, chyle fistula, flap failure, and lymphangioma in the field of head and neck surgery. We report a case of false vocal cord perforation with abscess successfully treated by negative pressure wound therapy after abscess treatment. The result suggests that negative pressure wound therapy can be an alternative or adjunctive approach for larynx perforation when the perforation is difficult to close after conservative therapy.